Investigation of the usage of nano-Titanium dioxide Produced with Polyethylene glycol and Alginate additives as nanofluid - Arslan, Reyhan; Akyol, Emel; Dalkilic, Ahmet Selim (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2024)
Purpose: The effect of synthesis conditions of TiO2 nanoparticles, surfactant type and concentration on the stabilization of the nanofluid was investigated. Nanofluids were measured from their thermophysical properties, stabilization and density. Theory and Methods: Nano titanium particles were synthesized by high temperature oxidation method with two different additives, PEG and alginate. 10% Titanium powder, 5% vegetable oil, 1% additive by weight were mixed in ultrasonic bath for 30 minutes. Then, the mixture in an alumina crucible was fed into a muffle furnace (Protherm), heated to a temperature of 900 degrees C at a rate of 10 degrees C /min and burned for 30 min. XRD, SEM, FTIR and BET measurements were used for the characterization of the synthesized TiO2 particles. Water-based nanofluids were prepared at different concentrations from synthesized nano titanium dioxides. Sodium dodecyl sulfate (SDS) and gum arabic were used to examine the effect of surfactant type and concentration on the stabilization of the nanofluid. Results: The results of XRD and FTIR analysis confirmed the formation of rutile TiO2. According to the SEM results, all the particles are nanocrystalline size. It was observed that the particles synthesized with both additives were homogeneously dispersed for at least 72 hours. It was observed that nanofluids produced by nanoparticles in the presence of alginate started to collapse after 96 hours. In addition, it was observed that the precipitation increased as the concentration increased. In the presence of PEG particles, precipitation, and interlayer formation were observed in some of the nanoparticles in the upper layer after 120 hours. Surfactants have been observed to increase stabilization. Conclusion: In conclusion, it was observed that the additives used in the production of nanoparticles affect the thermophysical properties of the nanofluid. As a result of the experimental studies, it was seen that TiO(2 )nanoparticles produced with Alginate additive were more successful in preparing and stabilizing nanofluids than those produced with PEG additive.
Keywords: Energy efficiency; Nanofluid; Titanium dioxide; Polyethylene glycol; Alginate; HEAT-TRANSFER; THERMAL-CONDUCTIVITY; VISCOSITY; PREDICTION; STABILITY; LIGHT; Engineering